Tega Industries : the South African acquisition - Aggarwal, Mayank, (SAGE business cases., 2020)
The case describes the international acquisition of the South African firm Beruc by an Indian, family-owned firm, Tega Industries Limited. Primarily a supplier of equipment to mining companies, Tega was a prominent player in the business of selling solutions to consumers in liners, mill liners, screening equipment and conveyors, apart from wear and flow equipment.Ten years after the acquisition, the benefits were not without problems. The issues facing the founder of Tega included declining financials of the subsidiary, labor-related problems, matters related to the supply chain, concerns from clients in South Africa, and sustained tensions between the local leadership and the corporate headquarters in India.With several changes in the leadership of the South African subsidiary (including Indian South African origin leaders), the ride was not smooth.